Novel cascading scheme of VSC‐HVDC with DC voltage synchronisation control for system frequency support - Xiaotian Yuan (Wiley, 2021)
Abstract This paper introduces a novel cascading frequency regulation scheme (CFRS) for VSC‐HVDC to provide strong support for the connected weak AC grid without phase‐locked loop and remote‐communication considering the cost‐effective property. The proposed CFRS utilises a DC voltage synchronisation control to enable the self‐synchronisation of VSC‐HVDC without phase‐locked loop, while the corresponding inertia response can be exerted via utilising the stored HVDC capacitor energy. Meanwhile, the DC voltage acts as the reflection of system frequency, enabling the coordination between two‐end VSC stations without communication. More importantly, to fully utilise the VSC‐HVDC potentials, the CFRS that sequentially activates HVDC capacitor and primary frequency control is implemented so that the energy loss and the detrimental control impacts on the sending‐end systems can be minimised while making sure the requirement of system frequency support. Analytical derivations have been done to evaluate the contribution of the proposed CFRS to system frequency regulation. Furthermore, the effectiveness of the proposed scheme has been well validated in PSCAD/EMTDC under several power system contingencies by fully comparing with existing control schemes. The proposed CFRS stands out by the reduced complexity of the control structure, the robustness for connecting the very weak AC grid and the fast frequency regulation ability with consideration of cost‐effective property.